Generation of three human induced pluripotent stem cell (hiPSC) lines from patients with Late-Onset Tay-Sachs disease (HEXA-related adult-onset GM2-gangliosidosis) - Gorka Fernández-Eulate; Céline Banal; Solène Renault; Nathalie Lefort; Yann Nadjar (Stem Cell Research)
Late-Onset Tay-Sachs (LOTS) disease is caused by mutations in the HEXA gene associated with a deficiency in the lysosomal enzyme β-hexosaminidase A, ultimately leading to an accumulation of ganglioside GM2. Tay-Sachs disease presents with heterogeneous neurological manifestations depending on age at onset, LOTS being specifically characterized by spinal motor neuron (SMN) degeneration. The c.805G > A (p.Gly269Ser) mutation in the HEXA gene is the most frequent in patients with LOTS and associated with a higher residual activity. Nevertheless, the mechanisms underlying SMN degeneration are unknown, given that there is no relevant experimental model to study LOTS.